Nghiên cứu tổng hợp và đặc trưng zeolit HZSM-5 dùng nguồn silic từ vỏ trấu - Hoài Nam và cộng sự, Lê Thị (Vietnam Journal of Chemistry, 2014)
HZSM-5 zeolite was successfully synthesized by hydrothermal treament using silica derived from rice husk. The sample was characterized by XRD, IR, SEM, TEM, BET and 27Al-NMR methods. Characterization results revealed that HZSM-5 material synthesized from rice husk silica has crystallinity and acidity as high as standard sample. Apart from the conventional pores system in ZSM-5 zeolite structure, another one which has kinetic diameter in range of 10-50nm (mesoporous system) in synthesized material structure was discovered. This pore system is expected to increase significantly the catalytic activity of synthesized material.